Kulturlandschaftliche Veränderungen in Harvatsko Zagorje (Kroatisch Zagorien), Jugoslawien - Crkvenčić, Ivo (ERDKUNDE, 1962)
The author trace the development of the agrarian landscape of North Western Croatia in an example from Croatian Zagorje from the first half of the 16th century up to today. He uses a retrogressive method commencing with the appearance of the contemporary agrarian land scape and agricultural structure and as the basic source of research drawing on cadastral maps (1860-1863 und 1894-1914) and land registry books. The results are compared with the laws which regulated the agrarian question. In Croatian Zagorje three natural elements can be distinguished: mountains, foothills and wide valleys. Of these three elements, however, settlement and cropland are predominantly found only on the foothills; the mountains are steep and the valleys are subject to flooding. The foothills were settled in two phases: the higher parts near the mountains by the early medieval colonisation and the lower parts of the foothills by the secondary colonisation from the middle of the 16th century. The present agrarian landscape of both parts of the foothills is characterized by hamlets whose small open fields are divided into tiny strips due to fragmentation. This area has the greatest density of population in Yugoslavia and agriculture cannot sustain the local population. The consequence of this is an especially strong migration which began in the middle of the 19th century, when fragmentation began. With the exception of the karst areas, there is no other area in Yugoslavia which has had such a strong migration. The agricultural structure and the agrarian landscape are of recent origin. Until the middle of the 19th century there prevailed in Croatian Zagorje isolated households with small enclosed fields, especially in the area of secondary colonisation. In the higher parts of foothills, settled in the early middle ages, were a small number of hamlets sorrounded by small openfields. The author stresses the characteristics of the land division of the above mentioned isolated holdings, giving basic data of their property relations. Then the problem of their origin is discussed particularly their dependance on the zadruga. He discusses facts which speak against the existing opinion that the isolated households with enclosed fields reflected the structure of zadruga as a typical slavic institution. He outlines reveals the socio-economic background of their creation and argues that on the contrary, there are indications of the dependance of the long mutual maintenance of zadruga and isolated holdings on enclosed fields, and the possible transition of eventual blood related zadrugas into nonrelated zadrugas as economic units. The reasons for the fast dissolution of isolated holdings with enclosed fields (in the period 1850-90) and their transformation into the existing hamlets with small open fields, are emplified shows that the abolishment of the zadruga was not the main factor of the division and fragmentation but that the most important facts lie in the difficult economic conditions after 1850, when division and fragmentation began. In conclusion he discusses the reasons and the consequences of the most recent changes of the agrarian landscape, mainly between 1890-1939.